Determination of 17alpha-hydroxypregnenolone sulfate and its application in diagnostics - Vceláková, Helena; Hill, Martin; Lapcík, Oldrich; Parízek, Antonín (Steroids, 2007)
New combined radioimmunoassay for determination of 17-hydroxypregnenolone sulfate (17-PregS) involving the hydrolysis of analyte by methanolysis was developed. 17-PregS, in addition to being secreted by the adrenals, is also formed by peripheral sulfoconjugation of 17-hydroxypregnenolone (17-Preg) or directly by hydroxylation of pregnenolone sulfate with 17alpha-hydroxylase/C17-20lyase. The measurement of 17-PregS can be used as a tool for detection of enzymatic deficiency particularly in pregnancy and for detection of congenital adrenal hyperplasia or gonadal dysfunction. The serum levels of 17-PregS, 17-Preg, dehydroepiandrosterone, dehydroepiandrosterone sulfate, pregnenolone and pregnenolone sulfate were measured in different age groups of human and in pregnant women respecting the age of gestation. The levels of 17-PregS are approximately three times higher than the levels of free 17-Preg in all subject groups. The levels of 17-PregS during pregnancy reached the local minimum in the 3rd month of gestation. The ratio of 17-PregS to free 17-Preg showed increasing profile during pregnancy with a maximum in the 8th month of gestation. These findings indicate that, the conversion of pregnenolone sulfate to 17-PregS is the major metabolic pathway for biosynthesis of 17-PregS.
Keywords: radioimunoanalýza; menstruační cyklus; Radioimmunoassay; těhotenství; mladiství; sexuální faktory; Gestational Age; Middle Aged; mužské pohlaví; Adult; dítě; Child; věkové faktory; gestační stáří; Child, Preschool; 17-alfa-hydroxypregnenolon; referenční hodnoty; ženské pohlaví; 17-alpha-Hydroxypregnenolone; Humans; předškolní dítě; Reference Values; Pregnancy; Sex Factors; lidé středního věku; Age Factors; Menstrual Cycle; dospělí; Female; Adolescent; lidé; Male